2022
DOI: 10.21203/rs.3.rs-1197456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exogenous plant growth regulator and foliar fertilizers for phytoextraction of cadmium with Boehmeria nivea [L.] Gaudich from contaminated field soil.

Abstract: (1) Background: As a enrichment plant, ramie can be used for the phytoremediation of cadmium (Cd)-contaminated soil. However, it is worth exploring the role of plant growth regulators and foliar fertilizers in the process of plant growth and development and Cd adsorption. (2) Methods: By measuring the agronomic traits, Cd content of aboveground and underground ramie, calculating the Cd transfer coefficient (TF) and Cd bioconcentration factors (BCF), and the correlation between various indicators. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Directly adding ABA to the cultural solution promoted ramie growth and development under Cd stress, increased Cd enrichment, and indicated its regulatory role in enhancement or stress tolerance and as a potential agronomic agent [73]. Similarly, another research team led by He et al [74] studied the effect of different growth regulators on the Cd content in ramie. The results showed that a foliar spray of hormones reduced the Cd content in underground parts of ramie, which showed the potential role of these growth regulators in increasing Cd tolerance [74].…”
Section: Agronomic Approaches To Enhance CD Tolerance In Ramiementioning
confidence: 97%
See 2 more Smart Citations
“…Directly adding ABA to the cultural solution promoted ramie growth and development under Cd stress, increased Cd enrichment, and indicated its regulatory role in enhancement or stress tolerance and as a potential agronomic agent [73]. Similarly, another research team led by He et al [74] studied the effect of different growth regulators on the Cd content in ramie. The results showed that a foliar spray of hormones reduced the Cd content in underground parts of ramie, which showed the potential role of these growth regulators in increasing Cd tolerance [74].…”
Section: Agronomic Approaches To Enhance CD Tolerance In Ramiementioning
confidence: 97%
“…Similarly, another research team led by He et al [74] studied the effect of different growth regulators on the Cd content in ramie. The results showed that a foliar spray of hormones reduced the Cd content in underground parts of ramie, which showed the potential role of these growth regulators in increasing Cd tolerance [74].…”
Section: Agronomic Approaches To Enhance CD Tolerance In Ramiementioning
confidence: 99%
See 1 more Smart Citation